2019
DOI: 10.1183/23120541.00043-2019
|View full text |Cite
|
Sign up to set email alerts
|

Xpert MTB/RIF performance to diagnose tuberculosis and rifampicin resistance in a reference centre in southern Brazil

Abstract: Effective treatment of tuberculosis (TB) remains a serious public health problem in many countries, including Brazil, especially when considering drug-resistant disease. Xpert MTB/RIF has been implemented in many countries to reduce the time to TB diagnosis and to rapidly detect rifampicin resistance. The study aimed to describe and evaluate Xpert MTB/RIF performance in diagnosing pulmonary TB and rifampicin resistance in a tertiary healthcare facility in Brazil.A cross-sectional study was performed, which inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
5
1
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 41 publications
2
5
1
1
Order By: Relevance
“…The discordance rate of Xpert–MGIT results found in this study is higher than reported in studies done in clinical settings that included symptomatic patients who sought care in health centers or were diagnosed with TB in Brazil (20%) [ 13 ], South Africa (15%) [ 11 ] and South Korea (26%) [ 12 ]. In contrast, our study regarded active case finding in the general population.…”
Section: Discussioncontrasting
confidence: 76%
See 1 more Smart Citation
“…The discordance rate of Xpert–MGIT results found in this study is higher than reported in studies done in clinical settings that included symptomatic patients who sought care in health centers or were diagnosed with TB in Brazil (20%) [ 13 ], South Africa (15%) [ 11 ] and South Korea (26%) [ 12 ]. In contrast, our study regarded active case finding in the general population.…”
Section: Discussioncontrasting
confidence: 76%
“…Xpert is an automated within-cartridge PCR that produces results within two hours. Numerous studies have shown that Xpert performs well compared with liquid culture for symptomatic patients in clinical settings, with its sensitivity to detect Mycobacterium tuberculosis (MTB) ranging from 82 to 95% [ 10 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Although the primary objective of this study was not to validate rapid molecular testing against the reference standard method, we compared the rate of RR-TB detected using GeneXpert MTB/RIF Assay with BD BACTEC TM MGIT TM 960 SIRE liquid culture system for automated drug susceptibility testing. The sensitivity of 100% of GeneXpert MTB/RIF Assay in detecting rifampicin resistance in our study was in line with previous studies reported by Meawed TE et al, (100%; [62] in Egypt, Jahan H et al, (98.5%; 2016) [63] in Bangladesh, Pandey P et al, (98.6%; 2017) [64] in Nepal and Mekkaoui L et al, (100%; 2021) [65] in Belgium; but higher than the sensitivity reported in previous studies by Tang T et al, (84.0%; 2017) [66] in China and Feliciano CS et al, (94%; 2019) [67] in Brazil. Whereas, the specificity of 94.6% of GeneXpert MTB/RIF Assay in detecting rifampicin resistance in our study was lower than previous study reported by Meawed TE et al, (100%; [62] in Egypt, Jahan H et al, (100%; 2016) [63] in Bangladesh, Pandey P et al, (100%; 2017) [64] in Nepal, Mekkaoui L et al, (99.2%; 2021) [65] in Belgium and Feliciano CS et al, (98%; 2019) [67] in Brazil; but higher than the specificity reported by Tang T et al, (87.8%; 2017) [66] in China.…”
Section: Discussionmentioning
confidence: 75%
“…However, as PCR was further developed, it became more affordable, versatile and reliable, with fully automated systems becoming commercially available from different companies [8][9][10]. For tuberculosis, routine tests using PCR reduced the turnaround time, allowing same day treatment initialization, which might impact resistance prevalence [11][12][13]. Cost-effective nucleic acid detection assays are relatively widespread, but assays for some neglected diseases are still missing.…”
Section: Introductionmentioning
confidence: 99%